Artificial war : multiagent-based simulation of combat - Ilachinski, Andrew (World Scientific Pub., 2004)
Military conflicts, particularly land combat, possess thecharacteristics of complex adaptive systems: combat forces arecomposed of a large number of nonlinearly interacting parts and areorganized in a dynamic command-and-control network; local action,which often appears disordered, self-organizes into long-range order;military conflicts, by their nature, proceed far from equilibrium;military forces adapt to a changing combat environment; and there isno master ""voice"" that dictates the actions of every soldier (i.